225k views
5 votes
Solve the equation. Write solutions using integers or simplified fractions.

4n−3=n+6

User Ezra Chu
by
5.7k points

2 Answers

2 votes

Answer:

n = 3

Explanation:

Given

4n - 3 = n + 6 ( subtract n from both sides )

3n - 3 = 6 ( add 3 to both sides )

3n = 9 ( divide both sides by 3 )

n = 3

User Fred Sauer
by
5.5k points
2 votes

Answer:

n = 3

Explanation:

4n - 3=n + 6

Collect like terms

4n - n = 3 + 6

3n = 9

Didvide both sides by 3

3n/3 = 9/3

n = 3

User Tarun Sharma
by
5.8k points